Streptomyces griseiviridis sp. nov., A Novel “Modern Actinobacteria” isolated from Malaysia Mangrove Soil - Law, Jodi Woan-Fei; Tan Loh, Teng Hern; Vengadesh, Letchumanan; Hong, Kar Wai; Ser, Hooi Leng *; Goh, Bey Hing *; Nurul Syakima, Ab Mutalib; Chan, Kok Gan; Lee, Learn-Han (HH Publisher, 2023)
A novel strain, Streptomyces griseiviridis MUM 136JT was recovered from a mangrove forest soil in Malaysia. The Gram-positive bacterium forms strong yellow aerial mycelium and moderate yellow substrate mycelium on ISP 2 agar. A polyphasic approach was used to determine the taxonomy status of strain MUM 136JT. The strain showed a spectrum of phylogenetic and chemotaxonomic properties consistent with those of the members of the genus Streptomyces. The cell wall peptidoglycan was determined to contain LL-diaminopimelic acid. The predominant menaquinones were identified as MK-9(H8) and MK-9(H6), while the identified polar lipids consisted of lipid, aminolipid, phospholipid, phosphatidylglycerol, phosphatidylinositol, phosphatidylethanolamine, diphosphatidylglycerol, and phosphatidylinositolmannoside. The cell wall sugars consist of ribose, mannose, and galactose. The predominant cellular fatty acids (>10.0 %) were identified as iso-C16:0 (31.6 %), anteiso-C15:0 (14.8 %), iso-C15:0 (12.0 %), and anteiso-C17:0 (11.1 %). Phylogenetic analysis identified that closely related strains for MUM 136JT are Streptomyces leeuwenhoekii DSM 42122T (98.9 %), Streptomyces erythrogriseus JCM 9650T (98.4 %), Streptomyces griseoincarnatus JCM 4381T (98.5 %). The DNA-DNA relatedness values between MUM 136 JT and closely related type strains ranged from 13.3 ± 1.5 % to 17.4 ± 2.0 %. The name Streptomyces griseiviridis sp. nov. is proposed, and the type strain is MUM 136JT (= NBRC 114249T = MCCC 1K04199T).